The patent buyout price for human papilloma virus (HPV) vaccine and the ratio of R&D costs to the patent value. - Mario Songane; Volker Grossmann (PLoS ONE, 2021)
Human papillomavirus (HPV) is responsible for almost all of the 570,000 new cases of cervical cancer and approximately 311,000 deaths per year. HPV vaccination is an integral component of the World Health Organization's (WHO) global strategy to fight the disease. However, high vaccine prices enforced through patent protection are limiting vaccine expansion, particularly in low- and middle-income countries. By limiting market power, patent buyouts could reduce vaccine prices and raise HPV vaccination rates while keeping innovation incentives. We estimate the global patent buyout price as the present discounted value (PDV) of the future profit stream over the remaining patent length for Merck's HPV vaccines (Gardasil-4 and 9), which hold 87% of the global HPV vaccine market, in the range of US$ 15.6-27.7 billion (in 2018 US$). The estimated PDV of the profit stream since market introduction amounts to US$ 17.8-42.8 billion and the estimated R&D cost to US$ 1.05-1.21 billion. Thus, we arrive at a ratio of R&D costs to the patent value of the order of 2.5-6.8%. We relate this figure to typical estimates of the probability of success (POS) for clinical trials of vaccines to discuss if patent protection provides Merck with extraordinarily strong price setting power.